Using a larval growth index to detect the environment-recruitment relationships and its linkage with basin-scale climate variability: A case study for Japanese anchovy (Engraulis japonicus) in the Yellow Sea - Qinwang Xing (Elsevier, 2021)
Increasing evidence has suggested that climate variability has a vital impact on the stock fluctuation of many small pelagic fishes by regulating their recruitment. However, most recruitment-related studies have focused on large spawning/nursing grounds at annual or seasonal scales, while few have considered the impact of short-term environmental variations during the vulnerable passive-transport period. In this study, a larval growth index based on a Lagrangian particle-tracking model coupled with a hydrodynamic model that focused on the early growth and passive transport of the SPF was developed to identify the key spawning/nursing period and grounds accommodating fish recruitment. Taking Japanese anchovy (Engraulis japonicus) in the Yellow Sea as an example, the key spawning grounds and time for its recruitment was identified and the impact of sea-surface temperature (SST) and climate variability on its recruitment was then investigated and discussed. Significant positive (negative) correlations were identified between the recruitment index and the mean growth index (mean water temperature) along the tracking path of eggs or larvae released in the Bohai Sea and the southwestern Yellow Sea during July (1987–2004), implying that these were the key spawning grounds and period for recruitment success. The multi-year tracking path of released particles indicated that both the southwestern Yellow Sea and the central Bohai Sea may be the key nursing grounds. Meanwhile, the SST in July was found to be associated with basin-scale atmosphere–ocean interactions. A potential “atmosphere–ocean-recruitment” influence pattern for Japanese anchovy in the Yellow and Bohai Seas was thus proposed, in which higher (lower) temperature during the key spawning/nursing period induced by atmospheric variation might diminish (promote) recruitment success by limiting the growth and survival of anchovy larvae. The larval growth index developed in this study can be widely applied to other small pelagic fishes in other waters and provide implications for climate-induced recruitment studies.